ARTICLE CAUSES OF FOREIGNIZATION (Лучшие интеллектуальные исследования, 2025)
Al-Khawarij (the rebels) were the first religious and political group to break away in Islamic history. In protest against Ali's decision to side with the neutrals in the Battle of Siffin, 12,000 men deserted his army, saying "only Allah can rule." They went to a place called Harura, not far from Kufa, and the sick were called "Haruri"